Implementasi Kepemimpinan Inklusif & Manajemen Perubahan pada Sekolah Multikultural: Analisis di SMPN 11 Muara Teweh - Shafa' Muthi'ah; Siti Mulkaf Lailawati; Dody Alfayed; Aslamiah; Celia Cinantya (Diklat Review : Jurnal manajemen pendidikan dan pelatihan, 2025)
This study aims to address the challenges of various changes in the world of education and develop the unique potential possessed by schools. This study uses a case study method to understand in depth how inclusive leadership practices are implemented and how change management is managed in a multicultural school environment. Data were obtained from direct observations of researchers and supported by documentary evidence, and analyzed to understand the best practices faced in the context of multicultural schools. The results of the study showed 5 important findings, namely inclusive leadership, change management, teacher involvement, student participation, community support, and academic and social outcomes. The role of the principal and stakeholders is very important in creating an inclusive and supportive environment in preserving culture at SMPN 11 Muara Teweh so that it becomes an important aspect in supporting change management. Keywords: Inclusive leadership, change management, multicultural school, SMPN 11 Muara Teweh